Sıçanlarda whey proteini ile oluşturulan glutatyon önkoþullandırmasının karaciğer sıcak iskemi/reperfüzyon hasarında hem oksijenaz-1 sistemi üzerine etkisi - GÜLLÜOĞLU, MAHMUT BAHADIR; ÇELİKEL, ÇİĞDEM (My University, 2008)
Purpose: Oxygen radicals which are produced during reperfusion phase play a central role for hepatocellular damage during ischemia/reperfusion (I/R) injury. Antioxidant strategies appear a promising approach to prevent I/R injury. In the present study, the effect of glutathione (GSH) preconditioning established by whey protein feeding on hepatocellular injury markers was assessed in a rat hepatic normothermic I/R injury model. The interaction between intracellular GSH content and heme oxygenase-1 (HO-1) enzyme expression was also determined in order to understand the level of upgrading of HO-1 system in a high GSH content environment after preconditioning.
The effect of glutathione preconditioning on heme oxygenase-1 system established by whey protein feeding on hepatocellular injury in a rat hepatic normothermic i/r injury model
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Liver; ischemia/reperfusion; whey; glutathione; heme oxygenase-1